Genotypes of John Cunningham (JC) Virus Urinary Excretion in Pregnant and Non-Pregnant Women in Isfahan, Iran - Sayyedeh Rahmaneh Atyabi; Majid Bouzari; Majid Komijani (Tehran University of Medical Sciences, 2018)
Objective: To evaluate presence of different subtypes and genetic variations of JC virus in different geographical areas is a useful tool for reconstructing of the genetic information and understanding of the evolution of the virus and also in tracing of the last and present history of human immigration. Materials and methods: This study aimed to investigate the reactivation of different genotypes of JC virus in kidney and its excretion in the urine of the 50 pregnant and 50 non-pregnant women. Phenol-chloroform method was used to extract DNA. Oligo 7 and MEGA 7 software were used for designing nested PCR specific primers based on vp1 capsid gene, and construction of phylogenetic tree, respectively. Fisher's exact test was used for statistical analyses. Results: All of the positive samples were sequenced and according to them, genotypes 1 and 3 of the virus were detected for the first time in pregnant and non-pregnant women in Asia. The frequency of genotypes 1 and 3 were 14.28% and 85.71% respectively. Conclusion: For the first time genotype 3 was reported as the frequent genotype in pregnant women in Asia. Confirming these needs more studies particularly with a higher number of cases and full genome sequencing of isolated JCVs.